(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تبحث هذه المقالة في تعديل خوارزمية أقرب جار، لإيجاد الحلول المثلى لمسألة البائع المتجول . إذْ وجدنا أن خوارزمية أقرب جار لا تعطي أفضل الحلول، وذلك بسبب مبدأ اختيار قاعدة البدء بالرحلة . إن تكلفة كل حل تتعلق بطريقة اختيار منطقة قاعدة الانطلاق. اعتمدنا في هذه الخوارزمية المعدلة على إيجاد حل موافق لكل منطقة انطلاق الرحلة وإيجاد التكلفة المقابلة، ثم اختيار الحل الأمثل من بين الحلول التي حصلنا عليها . This paper searching for improvement nearest neighbor algorithm, to find the optimum solutions for traveling salesman problem, since we found that the nearest neighbor algorithm did not give the best solution, because of the base choice principle to start the trip. The cost of each solution depends on the choice of the base area trip starting. In this improvement Algorithm, we depend on finding matching solution to each area of the trip areas and finding the related cost, then choosing the optimum solution from the solutions we obtained.